2021
DOI: 10.1186/s12905-021-01530-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of endometriosis in women undergoing laparoscopic surgery for various gynaecological indications at a Jordanian referral centre: gaining insight into the epidemiology of an important women's health problem

Abstract: Background Endometriosis is a considerable health challenge for women of reproductive age. Information about its prevalence in the Jordanian population is sparse. The objective of this research was to evaluate the presence of endometriosis in gynaecological patients undergoing laparoscopic surgery for various indications and to correlate the finding of endometriosis with variables, including patient demographics, obstetric history, type, and indication of laparoscopic procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…The prevalence of endometriosis is approximately 10% in women of reproductive age, and about 30% to 50% of women with endometriosis have infertility (Zondervan et al 2020;Muhaidat et al 2021;Smolarz et al 2021). However, this study showed that 70% of women with CSS were laparoscopically diagnosed with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of endometriosis is approximately 10% in women of reproductive age, and about 30% to 50% of women with endometriosis have infertility (Zondervan et al 2020;Muhaidat et al 2021;Smolarz et al 2021). However, this study showed that 70% of women with CSS were laparoscopically diagnosed with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Оскільки діагноз зазвичай підтверджується лише після лапароскопії, дані про безсимптомних пацієнтів, ймовірно, є недостатніми [60]. Крім того, епідеміологічні дослідження ендометріозу стикаються з низкою методологічних проблем, таких як визначення захворювання, упередження відбору та проблеми, пов'язані з проведенням когортних досліджень або досліджень випадок-контроль [42,61].…”
Section: результати й обговоренняunclassified
“…The causes of endometriosis have not yet been determined [ 3 ]. Endometriosis is associated with symptoms of dysmenorrhea, chronic pelvic pain, dyspareunia, dyschezia [ 4 ], up to 50% of women with endometriosis experience infertility [ 5 ] with an impairment of QoL [ 6 ]. Recent studies consider endometriosis as a disabling condition that may affect the social relationships, mental health, and sexual activity of women [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%